UPAYA PELESTARIAN TRADISI TENUN SONGKET DI DESA BUKIT BATU KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Winda Murniarti; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Desa Bukit Batu Kecamatan Bukit Batu Kabupaten Bengkalis. The purpose of this study was to determine the fabric artisans strategy songket maintain culture tenun in Desa Bukit Batu. The research titled “Tradition Preservation Efforts Tenun Songket in Desa Bukit Batu Kecamatan Bukit Batu Kabupaten Bengkalis”. Topics focus of this research is how the socio-economic circumstances craftsmen fabric songket in Desa Bukit Batu. Qualitative research is explained in detail through in-depth analysis of the subject under study. Therefore, in the determination of the samples using Pursposive Sampling technique, the authors set the number of research subjects as many as 5 people from the community Desa Bukit Batu and as a resource on the Village Head. So the sample in this study is as much as six research subjects. Strategy craftsmen fabric songket maintain culture weaving in the village of Bukit Batu is as follows: Biological Investment Strategy, this strategy made by weavers songket Bukit Batu by controlling the number of offspring that the needs of the economy remains stable and craftsmen do not need to find another job to cover the economic needs of the family because of the many family members / children must be financed. Successive strategy, this strategy is the most dominant strategy made the subject of research in an effort to maintain songket for direct inherited culture to the younger generations who will develop the teachings of his parents. used weaving Desa Bukit Batu with efforts to weave culture bequeathed directly to the younger generation in the family. Strateti educative, educational strategy is done by every family from generation to generation of weavers with teaching methods orally. As taught of how to see and care for the loom to use the loom. Economic investment strategy, this strategy made weaving by maintaining the quality and quantity of woven songket. The daily life of people in Desa Bukit Batu in paint with high solidarity, concern for others that is extraordinary. The economic situation weavers tend to be stable and affluent. It is characterized by wisdom weaving manage their income from savings. Keywords: Traditions, Tenun Songket, Culture